Students’ perceived learning and satisfaction with online learning in Japan during the COVID-19 pandemic - Sriyalatha, Mallika Appuhamilage Kumudini; Torii, Hiroshi; Kumarasinghe, Pivithuru Janak (Institute of Advanced Engineering and Science, 2024)
Moving from physical learning to online learning during the COVID-19 pandemic has opened many avenues to focus research on student perceived learning and satisfaction. This study examines the factors influencing the perceived learning and satisfaction of the students with online learning at university “A” in Japan during the COVID-19 pandemic. Primary data were collected via google form from 255 students in the field of social sciences at the university “A” in Nagoya, Japan using a structured questionnaire. R Studio and SPSS software were used to analyze the data. Internet access, learning platforms, and interaction were found to have a significant impact on perceived learning. Two variables; internet access and interaction have a positive impact on perceived learning, whereas learning platform has a negative significant impact on perceived learning. Policymakers and administrators in the higher education sector worldwide may benefit from these findings while formulation policies and strategies to support students during this pandemic and in a similar situation in the future.